EMPOWERING GOMBENGSARI COFFEE FARMERS TOWARDS SUSTAINABLE AGROTOURISM - Nurul Dwi Novikarumsari; Sri Subekti (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
This study aims to analyze the empowerment of coffee farmers in Gombengsari Village, Kalipuro District, Banyuwangi Regency in supporting sustainable agro-tourism. This study used a qualitative approach with data collection methods from in-depth interviews, and literature review. The results showed that the empowerment of Gombengsari coffee farmers involved various stakeholder roles, the goals are farmers will have a full level of empowerment.